Comparison of isatuximab-pomalidomide-dexamethasone versus elotuzumab-pomalidomidedexamethasone in relapsed/refractory multiple myeloma patients: a target trial emulation using real-world data - Enrica Antonia Martino; Annalisa Pitino; Massimo Offidani; Roberta Della Pepa; Alessandro Gozzetti; Velia Bongarzoni; Antonio Maroccia; Valeria Amico; Paola Stefanoni; Elena Zamagni; Sofia Terlizzi; Daniele Derudas; et al. (Haematologica)
Not available.